Assessment of quality of life in children with allergic rhinitis - N. E. Tarasova; A. A. Lebedenko; O. E. Semernik; A.-A. A. Kostornaya; E. V. Kabachenko; A. A. Rvacheva (Аллергология и Иммунология в Педиатрии)
Introduction. Atopic rhinitis (AR) affects 10–24 % of the population in Russia, often manifesting itself in early childhood. AR is as one of the most prevalent allergic diseases, significantly impacting children’s quality of life, affecting their physical health, psychoemotional well-being, as well as social and educational aspects of life.Materials and Methods. The study analyzed the responses from 43 children aged 6 to 17, presenting with exacerbations of allergic rhinitis. SNOT-22 test was used to assess the quality of life.Results. The study identified a substantial deterioration in the quality of life among patients suffering from allergic rhinitis. The analysis revealed that nasal discharge (rhinorrhea) affected 27 (63 %) of the participants, nasal congestion impacted 19 (44 %) individuals, sneezing affected 16 (37 %) patients, coughing affected 15 (35 %) patients, and postnasal drip was observed in 9 (21 %) of the participants. These symptoms significantly impacted the physical and psychoemotional well-being of children, as well as their social activity and academic performance.Conclusions. Hypoxia, induced by impaired ventilation of the respiratory tract, can negatively affect brain function, leading to decreased attention span, memory impairment, and cognitive dysfunction. The study results highlight the importance of a comprehensive approach to treating allergic rhinitis in children, which should encompass not only pharmacological interventions to alleviate symptoms but also educational programs both for parents and children. The SNOT-22 test proves valuable in everyday clinical practice for pediatricians and allergists, serving as an effective tool for dynamic monitoring both short-term and long-term effects of this condition’s therapy.